Communitarian therapy in university ambulatory - R. Neder, Christina; de Azevedo Pinheiro, Sandra (O Mundo da Saúde, 2010)
This paper evaluates the use of communitarian therapy in the waiting room of a clinics hospital aiming at emphasizing its value as a technique to care for patients. We want to present Communitarian Therapy as an efficient technique for use in the ambulatory setting. After the theoretical explanation of its applicability, we describe the experience done in three hospitals and its results.